1985
DOI: 10.1007/bf01851954
|View full text |Cite
|
Sign up to set email alerts
|

Preserved incretin effect after complete surgical denervation of the pancreas in young pigs

Abstract: Plasma insulin responses to intragastric (i.g.) (1.5 g/kg b.wt.) and "isoglycemic" intravenous (i.v.) glucose were measured in ten unanesthetized young pigs to assess the contribution of gastrointestinal factors to the total insulin secretion as observed after i.g. glucose. The participation of nerves was estimated by comparing metabolic tests performed before and after total surgical pancreatic denervation. In the five animals which survived the procedure, 52.6% of the insulin response after i.g. glucose was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…However, in another study, also in dogs, the incretin effect was preserved after pancreatic transplantation (62). In pigs, the incretin effect was unchanged after pancreas transplantation (63). The most likely explanation may be that both neural and endocrine mechanisms are operative.…”
Section: Discussionmentioning
confidence: 93%
“…However, in another study, also in dogs, the incretin effect was preserved after pancreatic transplantation (62). In pigs, the incretin effect was unchanged after pancreas transplantation (63). The most likely explanation may be that both neural and endocrine mechanisms are operative.…”
Section: Discussionmentioning
confidence: 93%
“…In patients with non–insulin‐dependent (type 2) diabetes mellitus (NIDDM) a reduced or absent incretin effect has been described (Nauck et al , 2003). In addition, in those patients, increased, rather than impaired, GIP secretion was observed (Nauck et al , 1985; Vaag et al ., 1996), and the responsiveness of the endocrine pancreas to GIP was greatly reduced due to underexpression of endocrine pancreatic GIP receptors (Holst et al , 1997). This reduced responsiveness to GIP is probably an early step in the pathogenesis of type 2 diabetes (Nauck et al , 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the slightly decreased pancreatic polypeptide level in the animals receiving transplants is consistent with maintenance of pancreatic denervation, and increased insulin secretion after transplantation may be a sequela of this situation. Higher maximum insulin levels and slightly higher incremental responses of insulin to an intragastric glucose load have also been reported after complete surgical denervation, in comparison with the innervated state of the pancreas [18,25]. Lugagne et al showed that portal and systemic venous drainage in streptozotocin-diabetic rats resulted in similar basal hyperinsulinemia in comparison with controls [22].…”
Section: Discussionmentioning
confidence: 81%